Localized provoked vulvodynia as an immune-mediated inflammatory disease: rationale for a new line of research - Paavonen, Jorma; Brunham, Robert C. (Frontiers in Cellular and Infection Microbiology, 2024)
Localized provoked vulvodynia (LPV), also called vulvar vestibulitis or provoked vestibulodynia, is a major cause of dyspareunia that severely impacts sexual health. At the tissue level, lymphocytic inflammation and hyperinnervation are characteristic pathological features, explaining the main symptoms and signs. A recent experimental animal study suggests that the histopathological findings of LPV may be due to mucosal CD4 Th17 immune responses to microbial antigens. We hypothesize that LPV is an immune-mediated inflammatory disease and challenge the concept of LPV as a chronic pain syndrome of unknown cause. Since most treatment modalities currently used in LPV are no better than placebo, we therefore warrant future research investigating the possible presence of CD4 Th17 cells and IL17 cytokine in affected tissues together with treatment trials that include inhibitors of the IL17 pathway.